2015
DOI: 10.1094/phyto-05-14-0152-r
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fungal Strain, Temperature, and Wetness Duration on Infection of Grapevine Inflorescences and Young Berry Clusters byBotrytis cinerea

Abstract: The effect of temperature and wetness duration on infection of Vitis vinifera inflorescences (from "inflorescence clearly visible" to "end of flowering" stages) and young berry clusters (at "fruit swelling" and "berries groat-sized" stages) by Botrytis cinerea was investigated. Artificial inoculations were carried out using conidial suspensions of eight B. cinerea strains belonging to the transposon genotypes transposa and vacuma. Infection incidence was significantly affected by strain but not by transposon g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…Some authors indicated that Botrytis conidia germination could occur at 13 • C [10], which explains the early infections that we detected during leaf development (S-1) at both vineyards in 2017. However, we detected that the highest Botrytis spore concentrations coincided with higher temperatures, around 20 • C and slightly rainy days, therefore within the optimal temperature range for infection development [45,55,56].…”
Section: Relationship With Phenological Stage and Meteorological Inflmentioning
confidence: 59%
“…Some authors indicated that Botrytis conidia germination could occur at 13 • C [10], which explains the early infections that we detected during leaf development (S-1) at both vineyards in 2017. However, we detected that the highest Botrytis spore concentrations coincided with higher temperatures, around 20 • C and slightly rainy days, therefore within the optimal temperature range for infection development [45,55,56].…”
Section: Relationship With Phenological Stage and Meteorological Inflmentioning
confidence: 59%
“…In the absence of inoculum, predicting disease occurrence based on infection periods would be ineffective and may result in excessive control applications if conditions do not favour other components (Madden and Ellis ). Therefore, when combined with predictive models for infection (Ciliberti et al , ) our equations could contribute to the development of an effective disease prediction system.…”
Section: Resultsmentioning
confidence: 99%
“…In Italy and Spain, most of the regional public sanitary services recommend spraying in B rather than in A to their viticulturists . On the other hand, some recent papers emphasize the importance of spraying at timing A rather than B …”
Section: Discussionmentioning
confidence: 99%
“…The biology of B. cinerea and its epidemiology on vine crops have been studied in detail, and multiple infection pathways have been identified that occur in two periods: from flowering to young cluster development, and after veraison. In the early season, B. cinerea infects inflorescences and young berries, resulting in (i) inflorescence and blossom blight, (ii) latent infections of berries, and (iii) saprophytic colonization of grape bunch trash . After veraison, latent infections may become visible as rotted berries, and the colonized bunch trash may serve as a source of inoculum inside the bunches.…”
Section: Introductionmentioning
confidence: 99%